2006
DOI: 10.1017/s0022112006001418
|View full text |Cite
|
Sign up to set email alerts
|

Thermal vibrational convection in near-critical fluids. Part 1. Non-uniform heating

Abstract: A theoretical model describing the response of a single-phase near-critical fluid to small-amplitude, high-frequency translational vibrations is developed on the basis of the multiple-scale and averaging methods. Additionally to the usual terms of thermal convection, the equations and boundary conditions contain new terms responsible for the generation of pulsating and average flows due to vibrational forcing and fluid compressibility. The effect of compressibility is taken into account both in the boundary la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…First, we write down the different orders of equations (19), (20) and (21). The first orders of the mass (19) and species balances (20) are as follows…”
Section: Separation Of the Processes Occuring On Different Time Scmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we write down the different orders of equations (19), (20) and (21). The first orders of the mass (19) and species balances (20) are as follows…”
Section: Separation Of the Processes Occuring On Different Time Scmentioning
confidence: 99%
“…Finally, we note that, firstly, the quick time-scale processes are damping and, secondly, there is no energy injection into fast processes as it could, for example, happen in the case of imposed high-frequency vibrations [20,21]. These two facts allow us to draw a conclusion that the short-term processes, even if existed at the initial moment, are to be rapidly damped out and are not to affect the long-term evolution on the convective and diffusive time-scales.…”
Section: Separation Of the Processes Occuring On Different Time Scmentioning
confidence: 99%
“…In recent decades, multiple studies have shown that an inertial field tuned from the outside can be a powerful tool for controlling heat and mass transfer processes in liquid media Gershuni and Lyubimov (1998); Allali et al (2002); Lyubimov et al (2006); Shevtsova et al (2010); . In this case, different types of inertial fields have distinct effects on the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic field impact on heat and mass transfer processes is the subject of thermoacoustic convection research in different mono‐ and heterophase hydrodynamic systems with high sensitivity to external effects. Thermal acoustic and vibrational convection is relevant in the study of heat and mass transfer in unstable media with complex rheology (eg, liquid metals, nonlinearly viscous media), 1,2 convective processes in near‐critical fluids 3 and in microgravitation, 4,5 and crystallization processes of binary solutions or melts 6,7 . Experimental and numerical studies also demonstrate significant acoustic field effects on the dynamics of heat convection in compressible media 8‐10 .…”
Section: Introductionmentioning
confidence: 99%